2022
DOI: 10.3390/ijerph19052995
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Walking Programs in Fibromyalgia: A Concordance Study between Measures

Abstract: This study analyzes the degree of agreement between three self-report measures (Walking Behavior, WALK questionnaire and logbooks) assessing adherence to walking programs through reporting their components (minutes, rests, times a week, consecutive weeks) and their concordance with a standard self-report of physical activity (IPAQ-S questionnaire) and an objective, namely number of steps (pedometer), in 275 women with fibromyalgia. Regularized partial correlation networks were selected as the analytic framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Second, this study is based on self-reported data; in this sense, a relevant limitation is presented by the walking having been assessed using self-reports. It should be noted in this regard that the current study is part of a larger project that previously assessed this same behavior by means of self-administered questionnaires and pedometers, and a high consistency was found between measures [ 67 , 68 , 69 ]. An additional shortcoming is the homogeneity of the sample, which was composed of only fibromyalgia patients.…”
Section: Discussionmentioning
confidence: 90%
“…Second, this study is based on self-reported data; in this sense, a relevant limitation is presented by the walking having been assessed using self-reports. It should be noted in this regard that the current study is part of a larger project that previously assessed this same behavior by means of self-administered questionnaires and pedometers, and a high consistency was found between measures [ 67 , 68 , 69 ]. An additional shortcoming is the homogeneity of the sample, which was composed of only fibromyalgia patients.…”
Section: Discussionmentioning
confidence: 90%
“…This method estimates parsimonious and interpretable network structure in the data, avoids spurious correlations, and handles relatively small datasets (Epskamp et al, 2018). The EBICglasso method was selected due to its applicability to non-normal variables via non-paranormal transformation and to ordinal variables via polychoric or polyserial correlations (Costantini et al, 2015;López-Roig et al, 2022). Continuous lines (i.e., edges) between variables (i.e., nodes) represent that they are related after controlling for all other variables, meanwhile the absence of lines means that variables are not related (Heino et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated in PwF that when PA self-efficacy levels increase, avoidance behavior is likely to reduce [33]. Psychologically informed physiotherapy, including a combination of interactive education sessions, graded activity, and problem-solving strategies might be effective in improving self-efficacy for PA in patients with widespread chronic pain [85].…”
Section: General Findingsmentioning
confidence: 99%